Development of Bdellophage VL-1 in Parasitic and Saprophytic Bdellovibrios - Kessel, Martin (1973)
Ultrastructure was correlated with growth kinetics of bdellophage VL-1 infecting host-dependent (“parasitic”) Bdellovibrio bacteriovorus 109J in its Escherichia coli B host (the three-membered system), as well as in the host-independent (“saprophytic”) derivative of the Bdellovibrio. Electron microscope observations showed the arrested growth of the phage-infected bdellovibrios, polar localization of the phage progeny, and stages in their release. Present evidence indicates that bdellophage DNA is derived from both the Bdellovibrio and its host cell.